Virtual Screening of Flavonoid Compounds against Angiotensin II Type I Receptor Using Docking Method - Fajriaty, Inarah; Arfimaz, Fahli; Riza, Hafrizal (Asian Journal of Chemistry, 2020)
The aim of this study was to determine the affinities and interactions of five flavonoids, namely quercetin, epicatechin, genistein, luteolin and hesperetin, against AT1R. Using the docking method, in silico studies were conducted, and AutoDock Vina and ChemOffice programs were used to analyse permeability and stability of atoms in the ligand. Discovery Studio was used for interaction visualization. Using ANOVA, ligand affinity was statistically analysed with 95% confidence level. The five flavonoids, namely quercetin, epicatechin, genistein, luteolin and hesperetin, and two positive controls, namely valsartan and losartan, had H donors < 5, H acceptors < 10 and molecular weights 302.24, 290.27, 270.24, 286.24, 302.28, 435.53 and 422.92 g/mol, respectively. Furthermore, the affinity of these ligands against AT1R were -8.3, -7.8, -8.3, -8.3, -7.6, -8.7 and -9.2 kcal/mol, respectively. Few amino acid residues showed interactions similar to the control, such as van der Waals, hydrogen bond and pi-interactions. All ligands in the normality and homogeneity tests showed p-values > 0.05 and equal to 0.059, respectively. The five flavonoids had p-value < 0.05 against the controls. All the five flavonoids have good permeability and their statistical affinity was significantly different from the controls. Nevertheless, active site cavities and amino acid residues similar to the controls enabled the flavonoids to interact with AT1R. The affinity of quercetin is statistically similar to that of genistein and luteolin, whereas that of epicatechin is similar to hesperetin.